Development of a Real-World Problem-Based Mathematics Module to Enhance Mathematical Modeling Skills - Dedi Sufriadi; Florianus Aloysius Nay; Shakira Ghazanfar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Many students find it difficult to connect abstract mathematical concepts with real-world applications, leading to limited problem-solving and modeling skills. This study aimed to develop a real-world problem-based mathematics module designed to enhance students’ mathematical modeling abilities. Using a Research and Development (R&D) approach with the 4D model Define, Design, Develop, and Disseminate the research involved secondary school students enrolled in mathematics classes. The Define stage identified learning difficulties and needs, while the Design and Develop stages focused on creating, validating, and refining a contextual mathematics module based on expert feedback. Quantitative data were collected through expert validation sheets, mathematical modeling tests, and student response questionnaires. The results demonstrated that the developed module achieved a high level of content and design validity, confirming its appropriateness for classroom use. Student responses indicated strong practicality and engagement during implementation. The effectiveness analysis showed a 28% improvement in mathematical modeling skills after the intervention, as evidenced by increased post-test scores and positive student feedback. Compared to traditional textbook-based instruction, the module proved more effective in fostering conceptual understanding, analytical reasoning, and real-world application of mathematics. In conclusion, the developed real-world problem-based module successfully bridges the gap between theoretical mathematics and authentic contexts, providing an innovative framework to cultivate modeling competence and critical thinking among students.